Pulpal expression of erythropoietin and erythropoietin receptor after direct pulp capping in rat. (2nd August 2022) - Papic, Milos; Zivanovic, Suzana; Vucicevic, Tamara; Papic, Mirjana V.; Zdravkovic, Dejan; Milivojevic, Nevena; Virijevic, Katarina; Zivanovic, Marko; Mircic, Aleksandar; Ljujic, Biljana; Lukic, Miodrag L.; Popovic, Milica
Abstract: This study aimed to evaluate the effect of direct pulp capping on the expression of erythropoietin ( Epo ) and Epo‐receptor ( Epor ) genes in relation to the expression of inflammatory and osteogenic genes in rat pulp. Dental pulps of the first maxillary molars of Wistar Albino rats were exposed and capped with either calcium hydroxide or mineral trioxide aggregate, or were left untreated. After 4 wk, animals were euthanized, and maxillae were prepared for histological and real‐time polymerase chain reaction analysis. Histological scores of pulp inflammation and mineralization, and relative expressions of Epo, Epor, inflammatory cytokines, and pulp osteogenic genes were evaluated. The capped pulps showed higher expressions of Epo, while the untreated pulps had the highest expression of Epor . Both calcium hydroxide and mineral trioxide aggregate downregulated the expression of tumor necrosis factor alpha compared to untreated controls, and upregulated transforming growth factor beta compared to healthy controls. Alkaline phosphatase expression was significantly higher in experimental groups. Relative expression of Epo negatively correlated with pulp inflammation, and positively correlated with pulp mineralization. Pulp exposure promoted expression of Epor and pro‐inflammatory cytokines, while pulp capping promoted expression of Epo, alkaline phosphatase, and downregulated Epor and pro‐inflammatory cytokines.